2016
DOI: 10.1111/jfd.12566
|View full text |Cite
|
Sign up to set email alerts
|

A simplified method to estimate Diphyllobothrium spp. infection in salmonids

Abstract: Some fish parasites constitute severe management problems as they may cause mortality of their fish host or are important zoonoses of humans. Parasite assessments are therefore critical to keep track of infections. If conventional sampling techniques can be simplified, parasite assessments might be easier to obtain, less time-consuming and more extensive. In this study, we compare the assessed number of Diphyllobothrium spp. cysts (CYST) with the counted number of Diphyllobothrium spp. plerocercoid larvae reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…dendriticum and D . ditremum , and cyst counts provide a reliable estimate of their combined total number 24 . Intestines were frozen and later screened for parasites as described by Kuhn et al ., (2017).…”
Section: Methodsmentioning
confidence: 99%
“…dendriticum and D . ditremum , and cyst counts provide a reliable estimate of their combined total number 24 . Intestines were frozen and later screened for parasites as described by Kuhn et al ., (2017).…”
Section: Methodsmentioning
confidence: 99%
“…cysts on the stomach wall was counted. There are two species of Diphyllobothrium present in charr from these systems, D. dendriticum and D. ditremum, and cyst counts provide an estimate of their combined total number (Kuhn et al, 2017). Both Diphyllobothrium parasites are trophically transmitted to charr via ingestion of infected copepods or small fish that are paratenic hosts (Halvorsen, 1970;Henriksen et al, 2016).…”
Section: Parasite Samplingmentioning
confidence: 99%
“…in whitefish (cf. Hoffman 1999, Kuhn et al 2017). This has facilitated the collection of several years of data within a monitoring programme with restricted resources, but the data recorded are minimum values both for prevalence, infection intensity and abundance.…”
Section: Discussionmentioning
confidence: 99%
“…This has facilitated the collection of several years of data within a monitoring programme with restricted resources, but the data recorded are minimum values both for prevalence, infection intensity and abundance. Kuhn et al (2017) demonstrated that counting cysts of Diphyllobothrium spp. on the stomach, viscera and on the walls of the body cavity, in the same way as we have done, provided a reliable estimate of prevalence, intensity and abundance of the parasite.…”
Section: Discussionmentioning
confidence: 99%